An empirical analysis of 4 aspects of board composition in Singapore public-listed companies. - Koh, Hwee Hong. (2008)
The report presents an empirical analysis of the 4 aspects of board composition-board independence, multiple drectorship,directors' skills, knowledge and expertise and their nationalities. We study how these four aspects contribute to the importance of having a good board of directors inthe respective sections. Our sample includes 404 Singapore Public-Listed companies as at 31 December 2001.